The influence of infrastructure quality on usage smart mobile applications and digital payments - Fahmi Alamsyah; Indrianawati Usman; Yetty Dwi Lestari (Sustainable Futures, 2025)
This paper aims to examine what variables influence the use of digital technology-based payment tools, whether infrastructure networks or smart applications will influence it. This research tests whether the quality of infrastructure affects the use of smart applications and also to see the effect of infrastructure networks on the use of digital payment tools. This study uses a quantitative method, the questionnaire was distributed to 150 samples. The number of those who filled out and returned the questionnaire was 118 samples, so the sample participating in this study was 118 respondents. With partial least squares structural equation modeling, the questionnaire results were then collected and processed using PLS-SEM to examine the relationship between variables. This research finds that quality infrastructure encourages the use of smart applications and encourages the use of digital payment tools. Infrastructure networks have a positive and significant influence on smart applications. Likewise, infrastructure networks have a positive and significant influence on the use of digital payment tools now and in the future. This study shows that the increasing diversity of smart applications and increasing payment transactions via digital payment tools, one of the determining factors is because it is influenced by the availability, distribution and quality of infrastructure networks. Digital technology-based payment tools are still open for research. Contribution to the understanding of the need for a distributed and quality infrastructure network, as well as the availability of smart applications can be a determinant of the use of digital payment tools.